Dilute Acid Pretreatment And Enzymatic Hydrolysis Of Lignocellulosic Biomass For Butanol Production As Biofuel - Devitra Saka Rani; Cut Nanda Sari (Testing Center for Oil and Gas LEMIGAS, 2012)
Biobutanol is one of the promising biofuel for substituting gasoline. Biobutanol produced from biomass fermentation using solventogenic clostridia which are able to convert a wide range of carbon sources to fuels such as butanol. Therefore, lignocellosic biomass has great potential as fermentation substrate for biobutanol production. Lignocellosic biomass should be hydrolized before fermentation by a pretreatment process and enzymatic hydrolysis. The various lignocellulosic biomass pretreatment will infl uence in butanol production depending on fermentable sugars content. The objective of this research is to get potential lignocellulosic biomass using dilute acid pretreatment and enzymatic hydrolysis process for biobutanol production. Eight types of biomass from sugarcane bagasse, rice straw, rice husk, empty fruit bunch (EFB) of palm oil, corn cob, pulp waste, traditional market organic waste, and microalgae were used in this experiment. After hydrolysis, the high result of total fermentable sugars in corn cobs, bagasse, rice straw, and rice husk, shows good opportunity of these biomass to be used as fermentation feedstocks for biobutanol production. In addition, pulp waste, organic waste, and microalgae are prospective as raw material but require more appropriate treatment either for to break down the cellulose/hemicellulose or to enhance reducing sugar content. Fine milling and delignifi cation have no signifi cant effect on cellulosic biomass conversion into fermentable sugars. Therefore, the production cost can be reduced. In order to enhance the sugar content and reduce the formation of inhibitor product, it is necessary to examine dilute acid pretreatment variations and appropriate operating conditions of enzymatic hydrolysis process